BRAF kinase domain mutations are present in a subset of chronic myelomonocytic leukemia with wild‐type RAS. Issue 5 (10th February 2014) - Zhang, Liping; Singh, Rajesh R.; Patel, Keyur P.; Stingo, Francesco; Routbort, Mark; You, M. James; Miranda, Roberto N.; Garcia‐Manero, Guillermo; Kantarjian, Hagop M.; Medeiros, L. Jeffrey; Luthra, Rajyalakshmi; Khoury, Joseph D.
<x xml:space="preserve">Abstract</x> The frequency of RAS mutations in chronic myelomonocytic leukemia (CMML) suggests that activation of the MAPK pathway is important in CMML pathogenesis. Accordingly, we hypothesized that mutations in other members of the MAPK pathway might be overrepresented in RASwt CMML. We performed targeted next generation sequencing analysis on 70 CMML patients with known RAS mutation status. The study group included 37 men and 33 women with a median age of 67.8 years (range, 28–86 years). Forty patients were RASwt and 30 were RASmut; the latter included KRAS = 17; NRAS = 12; KRAS + NRAS = 1. Five patients (7.1% of total group; 12.5% of RASwt group) with RASwt had kinase domain BRAF mutations. The BRAF mutations were of missense type and involved exon 11 in one patient and exon 15 in four patients. All BRAFmut patients had CMML‐1 with low‐risk cytogenetic findings. Two (40%) of the five patients with BRAFmut patients transformed to acute myeloid leukemia during follow‐up. In summary, we demonstrate that a subset of patients with RASwt CMML harbors BRAF kinase domain mutations that are potentially capable of activating the MAPK signaling pathway. Am. J. Hematol. 89:499–504, 2014. © 2014 Wiley Periodicals, Inc.